Risk Factors Analysis of Typhoid Fever Occurence of Inpatient in Kebumen Public Hospital in 2013 - Rina Hudayani; Hari Kusnanto; Rizka Humardewayanti; Trisno Agung Wibowo (Pusat Kedokteran Tropis, 2013)
ABSTRACTIntroduction: Typhoid fever is a disease caused by infection of Salmonella typhoid and paratyphoid bacteria. There are 350-810 people who get this disease per 100.000 people and the percentage of death is 0.6-5%. Typhoid fever in Kebumen Regency always belongs to the big five diseases. The criteria are the number of in-patient in the hospital and the extraordinary occurrence for 4 years (from 2007 to 2010). This disease is related to unhealthy sanitation and bad individual hygiene practice.Objective: To analyze the risk factors of typhoid fever occurrence of inpatient in Kebumen Public Hospital in 2013.Methods : This research is an analytical observational research with control case study design. The sample subject was taken by using consecutive sampling method and there were 148 respondents, consisting of 74 case respondents and 74 control respondents. The data were analyzed by using McNemar (bivariate) test and conditional logistic regression (multivariate).Results : Most respondents are in the age of 15-20 years old (32.43%), female (70.27%), the graduates of Senior/Vocational High School (29.05%) and student/university student (34.46%). The results of multivariable analysis are the risk factor of eating non-homemade snack habit is high (p=0.000; OR=5.586; CI 95% 2.142-14.571) followed by the habit of washing hands before eating (p=0.003;OR=2.835; CI 95% 1.433-5.609). Water clean sources, facility for defecation, defecation habit in latrine, and typhoid fever history in family are not the risk factors of typhoid fever occurrence of in-patient in Kebumen Public Hospital.Conclusion : The risk to get typhoid fever in Kebumen Regency is higher on those whose habits of eating non-homemade snacks and not washing hand by using soap before eating. Therefore, the health officer should improve individual hygiene promotion and give information to society and those who manage food processing public place.Key Words: Risk factors,Typhoid fever, Kebumen.